Strategic-based regional development: Towards a theory of everything for regional development? - Medeiros, E. (European Journal of Spatial Development, 2022)
This paper presents a potential ‘theory of everything’ for regional development processes which can be applied to development and cohesion policies. Denominated as strategic-based regional development, this more comprehensive regional development theoretical background embraces several established regional development paradigms, which include sustainable-, institutional-, knowledge-, place-, infrastructural-, and balanced-based policy rationales. Strategic-based regional development aims to respond to the development challenges and needs of all regions by embracing not only socioeconomic and environmental policy actions, but also spatial planning and governance-related policy approaches. Drawn mostly on desk research, the presented theoretical rationale draws a distinction between mainstream regional development theories since it builds upon the territorial development concept, rather than the economic development